Analysis of Maqāṣid Syarī‘ah on the Time Value of Money: A Study on the Practice of Money-Based Arisan - Nindhi Fitria Ningrum; Nikmatul Masruroh; Hersa Farida Qoriani (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, transactions in Islamic economics emphasize justice (‘adl) and the protection of wealth (ḥifẓ al-māl). However, in reality, the practice of money-based rotating savings (arisan uang) in society contains implications of the Time Value of Money (TVM), which may lead to value disparities among participants. This study aims to analyze the practice of money-based arisan from the perspective of Maqāṣid Syarī‘ah, particularly in relation to transactional justice and the protection of wealth. This article is categorized as a juridical-empirical legal study employing a qualitative approach. The methodology used is descriptive analytical within the framework of Islamic economic law. The findings indicate that money-based arisan implicitly contains the principle of TVM through differences in the timing of fund receipt, where early participants obtain higher economic value. This practice does not involve riba as there is no stipulated monetary increment. From the perspective of Maqāṣid Syarī‘ah, arisan is considered permissible as long as it fulfills the principles of ta‘āwun (mutual assistance), transparency, and distributive justice. However, the potential for gharar remains if disparities arising from the time value of money are not managed fairly.